Makna Gembala dalam Kitab Mazmur 23 - Daniel Boedhi Oetomo (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This article presents the meaning of the shepherd in the book of Psalm 23. The meaning of the shepherd today needs to look deeply at what is written in the book of Psalm 23, so that they can emulate what the psalmist wrote. By using a qualitative approach, descriptive method, and literature study as a data collection tool, it was found that the shepherd in the book of Psalm 23 is described by God as a shepherd who cares for and fulfills all the main needs of his sheep. Today's pastors have the task of leading the congregation with an example in life, paying attention to the physical and spiritual needs of the congregation. Pastors must now know the congregation they serve.